2022
DOI: 10.3390/ani12192644
|View full text |Cite
|
Sign up to set email alerts
|

WGCNA Analysis of Important Modules and Hub Genes of Compound Probiotics Regulating Lipid Metabolism in Heat-Stressed Broilers

Abstract: This study aimed to study compound probiotics’ (Lactobacillus casei, Lactobacillus acidophilus and Bifidobacterium) effects on production performance, lipid metabolism and meat quality in heat-stressed broilers. A total of 400 one-day-old AA broilers were randomly divided into four groups, each containing the same five replicates, with 20 broilers in each replicate. The control (21 °C) and experiment 2 were fed a basic corn–soybean meal diet. Experiment 1 (21 °C) and experiment 3 were fed a basic corn–soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…FKBP10 is a member of the FK113 binding protein gene family and is involved in many functions, including protein folding and repair in response to heat stress, which is necessary to maintain natural peptides and prevent protein aggregation ( Akbarzadeh et al, 2018 ). Our previous research found that heat stress can affect lipid metabolism and increase cholesterol content in broilers ( Zhang L. et al, 2022 ). Studies have found that LBP (lipopolysaccharide binding protein) has been used as an indicator of the impairment of intestinal barrier function, and its level can reflect the degree of intestinal leakage ( Vancamelbeke and Vermeire, 2017 ; Wu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…FKBP10 is a member of the FK113 binding protein gene family and is involved in many functions, including protein folding and repair in response to heat stress, which is necessary to maintain natural peptides and prevent protein aggregation ( Akbarzadeh et al, 2018 ). Our previous research found that heat stress can affect lipid metabolism and increase cholesterol content in broilers ( Zhang L. et al, 2022 ). Studies have found that LBP (lipopolysaccharide binding protein) has been used as an indicator of the impairment of intestinal barrier function, and its level can reflect the degree of intestinal leakage ( Vancamelbeke and Vermeire, 2017 ; Wu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that LAB could significantly improve lipid metabolism and fat deposition ( Cho et al, 2020 ; Wang et al, 2023 ). Zhang et al (2022) report that LAB have an effect on production performance, lipid metabolism, and meat quality in heat–stressed broilers. Previous studies have shown that LAB can increase the bacterial phylogenetic diversity in the gut of mice ( Usui et al, 2018 ) and weaning piglets ( Zhao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of focusing on a single gene, WGCNA intends to extract hub genes from co-expression networks to preferably investigate the biological regulations. Recently, WGCNA method was popularly applied, and mounting genes were found to participate in various lipid related processes, including obesity, adipogenic differentiation of stem cell, polyunsaturated fatty acid ( Han et al, 2020 ; Liu et al, 2021 ; Xiao et al, 2022 ; Zhang et al, 2022 ). Although the study on gene profiles in subcutaneous adipose tissue at four developmental stages in Ningxiang pigs has been reported ( Gong et al, 2021 ), the underlying molecular mechanism of subcutaneous adipose tissue development in different periods is still unclear.…”
Section: Introductionmentioning
confidence: 99%